Challenges And Opportunities For EFL Instruction With An Islamic Perspective - Kalayo Hasibuan; Salsabila Ramadhani Salsabila; Santy Agustin Agustin; Silvi Ramadhani Ramadhani; Siti Maulani Delfina Delfina (Journal of Innovative and Creativity, 2025)
This article explores the integration of Islamic values into English as a Foreign Language (EFL) instruction, emphasizing both the challenges and opportunities within Islamic educational contexts. As English serves as a global language for communication and knowledge, embedding Islamic principles into EFL teaching adds a moral and spiritual dimension to language learning. The paper draws on qualitative literature and empirical studies to propose strategies for addressing cultural, ideological, and material-related barriers. It highlights the importance of aligning language instruction with the cultural and spiritual backgrounds of Muslim learners through character education, teacher training in faith-based pedagogy, and the inclusion of Islamic content in teaching materials. Furthermore, the integration of educational technology and media such as multimodal digital content and Islamic-themed instructional tools is explored as a means to enhance both linguistic competence and moral development. This holistic approach aims to cultivate not only language skills but also critical thinking, intercultural awareness, and ethical values among learners.